A Comprehensive Review on Vranashotha: An Ayurvedic Perspective on Inflammatory Wound Management - Dr. Bhargav Patel,; Dr. Shailesh R Jaiswal, (The Bioscan, 2026)
Background: Vranashotha is an Ayurvedic term used to describe localized inflammatory swelling that occurs in or around a wound (Vrana). It results from the vitiation of Tridoshas (Vata, Pitta, and Kapha) due to factors like trauma, infection, improper dietary practices, systemic diseases, or surgical complications. Classical Ayurvedic texts such as the Sushruta Samhita provide detailed descriptions of the stages, causes, symptoms, and treatment of Vranashotha, which closely resemble modern concepts of inflammation. Aim: To present a comprehensive review of the Ayurvedic understanding of Vranashotha, correlate it with modern inflammatory pathology, and outline integrated approaches for its effective management. Methods: This review critically analyzes Ayurvedic classical references from texts such as Sushruta Samhita and Ashtanga Hridaya, and compares them with current biomedical literature on inflammation. Ayurvedic treatment protocols, formulations, and therapies have been reviewed alongside modern medical interventions to establish a comparative framework. Results: Vranashotha is classified into Ama (immature), Pachyamana (suppurative), and Pakva (mature abscess) stages. Symptoms such as redness (Raga), heat (Ushna), swelling (Shotha), and pain (Vedana) are common to both Ayurveda and modern inflammation. Management in Ayurveda includes internal medicines like Trivrit Churna, Punarnava, Guggulu, and Triphala, along with external therapies such as Swedana (sudation), Lepa (herbal paste), and Jalaukavacharana (leech therapy). Modern management typically includes antibiotics, NSAIDs, and surgical drainage. Conclusion: Vranashotha serves as a classical example of the convergence between traditional Ayurvedic and modern biomedical concepts of inflammation. With its holistic, stage-wise therapeutic strategies, Ayurveda offers a valuable, complementary approach to managing wound-related inflammatory conditions. Integrative management, combining Ayurvedic wisdom with modern surgical and pharmaceutical care, holds promise for improved outcomes in chronic or complicated wound inflammations.